2016
DOI: 10.1159/000438632
|View full text |Cite
|
Sign up to set email alerts
|

TOB1 Deficiency Enhances the Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Tendon-Bone Healing in a Rat Rotator Cuff Repair Model

Abstract: Background/Aims: This study investigated the effect of silencing TOB1 (Transducer of ERBB2, 1) expression in bone marrow-derived mesenchymal stem cells (MSCs) on MSC-facilitated tendon-bone healing in a rat supraspinatus repair model. Methods: Rat MSCs were transduced with a recombinant lentivirus encoding short hairpin RNA (shRNA) against TOB1. MSC cell proliferation was analyzed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. The effect of MSCs with TOB1 deficiency on tendon-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…Further, the animal model used may not be suitable for investigating structural and biomechanical improvement of tendons for an extended period after surgery. We and others [12,30] observe the formation of chondrified areas within the defect area after 28 days, which eventually result in the formation of irreversible ectopic mineralization in the neotissue, ultimately hampering biomechanical analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Further, the animal model used may not be suitable for investigating structural and biomechanical improvement of tendons for an extended period after surgery. We and others [12,30] observe the formation of chondrified areas within the defect area after 28 days, which eventually result in the formation of irreversible ectopic mineralization in the neotissue, ultimately hampering biomechanical analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Light emitting diode (LED)-based therapy, a non-invasive biophysical therapy, has been widely and successfully used in clinical practice for several diseases, including arthritic pain [8], osteoarthritis [9], rheumatoid arthritis [10], skin rejuvenation [11], and wound healing [12,13]. Recent studies have already demonstrated that red LED irradiation has beneficial effects on bone marrow-derived MSCs (BMSCs) proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of TGF-βs/BMPs with TGF-β specific type 1 and type 2 or BMP serine/threonine kinase receptors initiates the signaling cascade via canonical (or Smad-dependent pathways) and non-canonical pathways (or Smad-independent signaling pathways) [50]. The TGF-β/BMP signaling pathway plays an important regulatory role in bone repair [51-56]. It is also confirmed to be involved in PEMF-induced osteogenesis.…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%